Analysis of Compensation, Work Environment, and Company Culture on Employee Job Satisfaction at PT Adira Dinamika Multi Finance Medan Branch 3 - Harsya Rasta Dewa; Saimara A.M Sebayang; Darmilisani Darmilisani (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the effect of compensation, physical work environment, and corporate culture on employee job satisfaction at PT Adira Dinamika Multi Finance Medan 3 branch. This study employed a quantitative approach with an associative method. The research population consisted of 65 employees, with a sample of 65 respondents selected using a saturated sampling technique. Primary data were obtained through the distribution of questionnaires, and the results were processed using SPSS software version 24. Data analysis was conducted using multiple linear regression to examine the relationship between independent variables and the dependent variable. The results showed that compensation, physical work environment, and corporate culture, both partially and simultaneously, had a positive and significant effect on employee job satisfaction. Compensation had a regression value of 0.395, a t-value of 4.877, and a significance value of 0.000. The physical work environment had a regression value of 0.292, a t-value of 3.393, and a significance value of 0.001. Corporate culture had a regression value of 0.236, a t-value of 2.912, and a significance value of 0.005. Simultaneously, the F-value was 233.927 with a significance value of 0.000. Compensation became the most dominant variable influencing job satisfaction with the highest regression value. The coefficient of determination (adjusted R²) of 0.916 indicated that 91.6% of the variation in job satisfaction was explained by the three independent variables. In addition, the strength of the relationship between the independent variables and the dependent variable was classified as very strong, with a correlation coefficient (R) of 0.959.